An ex-ante impact assessment of Striga control technology for sorghum production in Ethiopia - Kassie, Mengistu (Kansas State University, 2019)
Sorghum (Sorghum bicolor L. Moench) is an important food security cereal crop in Sub-Saharan Africa (SSA). It is produced under adverse conditions such as low rainfall, arid and semi-arid environments which makes it the important food security crop in East Africa where agriculture and environmental conditions are unfavorable to produce other cereals. In Ethiopia, sorghum is the third most important staple crop next to teff and maize. The production of sorghum in Ethiopia is hampered by biotic and abiotic factors. Drought is the most important abiotic factor for sorghum production in Ethiopia. The parasitic weed, Striga spp., is a major biotic factor affecting the production of sorghum where the impact sometimes is reported a total crop damage. The objective of this study was to undertake an ex-ante impact assessment of Striga control technology for sorghum production in Ethiopia. Based on the economic surplus method, we have estimated the economic contribution of a sorghum supply shock as a result of the Striga control technology. We used the World Bank LSMS-ISA 2013/14 data as a base year to simulate the welfare effect of different scenarios on yield, adoption cost, adoption rate and probability of success. Sorghum, being a non-traded crop, the increase in supply as a result of the Striga control technology reduces the producer’s surplus and increases the consumer’s surplus. We have shown the impact of Striga control technology on farmer’s welfare in ten different scenarios. In all the ten scenarios, producers will have a negative surplus even though the Striga control technology is assumed to increase sorghum production by 65%. However, the consumer surplus is positive. Since sorghum producers are also consumers, the net benefit of adopting the new technology is positive.
Keywords: Sorghum; Striga; Ethiopia; Technology